2021
DOI: 10.21924/cst.6.1.2021.293
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cr(VI) from aqueous solution by biochar derived from rice husk

Abstract: In this work, biochar produced from Indonesian rice husks. Then used as adsorbent of Cr(VI) in aqueous solution. The XRD pattern of biochar showed the characterization pattern at 23º (002) reflection, appearance of silicate oxide, and the carbon vibrations. The surface area and SEM morphologies confirmed that after pyrolysis treatment the surface of rice husk has changed. The surface area of biochar increased after thermal treatment. The adsorption study of Cr(VI) by biochar demonstrate 2nd-order reaction, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This research characterizes rambutan skin (Nephelium lappaceum L) using an FT-IR spectrophotometer which produces a vibration peak at 1716.61 cm -1 which indicates the presence of a non-ionic carbonyl group (C=O) (Zhang et al, 2018). At the peak of 3419.33 cm -1 there is a group (O-H) derived from the alcohol and carboxylic acid groups (Mohadi, Palapa, Taher, et al, 2021). Characteristics of the successful preparation of rambutan peel as an adsorbent was supported by adsorption-desorption analysis of nitrogen which resulted in isotherm patterns, data on surface area, pore volume, and pore diameter.…”
Section: Resultsmentioning
confidence: 98%
“…This research characterizes rambutan skin (Nephelium lappaceum L) using an FT-IR spectrophotometer which produces a vibration peak at 1716.61 cm -1 which indicates the presence of a non-ionic carbonyl group (C=O) (Zhang et al, 2018). At the peak of 3419.33 cm -1 there is a group (O-H) derived from the alcohol and carboxylic acid groups (Mohadi, Palapa, Taher, et al, 2021). Characteristics of the successful preparation of rambutan peel as an adsorbent was supported by adsorption-desorption analysis of nitrogen which resulted in isotherm patterns, data on surface area, pore volume, and pore diameter.…”
Section: Resultsmentioning
confidence: 98%
“…The increasing temperature has made the viscosity of the liquid decreased and the rate of diffusion in adsorbate through boundary layer and internal pore of the adsorbent increased [43]. This tendency occurred when the saturation value was attained, and the adsorption was considered to be promoted by high temperature and occupied an inactive site onto adsorbents [44] The enthalpy parameter (∆H o ) predicted the adsorption mechanisms such as chemisorption or physisorption. The result showed that the enthalpy value of 75.2084 kJ/mol included in the range of 20.9 < H o < 418.4 kJ/mol, showing that the adsorption is included in chemical adsorption [42].…”
Section: Thermodynamic Studymentioning
confidence: 99%
“…Hydrochar has a chemical composition, which is similar to coal at the lowest level such as peat or lignite (Kantakanit et al, 2018;Mlonka-Mędrala et al, 2022). Hydrochar has many uses, one of which can be used as a pollutant-absorbent material Islam et al, 2017. Hydrochar is a material that has a high carbon content and is rich in oxygenated functional groups such as hydroxyl, carbonyl, or carboxylate, with high hydrophilic properties and good chemical reactivity (Zhang et al, 2017;Mohadi et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%